2008
DOI: 10.1158/0008-5472.can-07-2559
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-I–Dependent Up-regulation of ZEB1 Drives Epithelial-to-Mesenchymal Transition in Human Prostate Cancer Cells

Abstract: The epithelial-to-mesenchymal transition (EMT) is crucial for the migration and invasion of many epithelial tumors, including prostate cancer. Although it is known that ZEB1 overexpression promotes EMT primarily through down-regulation of E-cadherin in a variety of cancers, the soluble ligands responsible for the activation of ZEB1 have yet to be identified. In the present study, we investigated the role of insulin-like growth factor-I (IGF-I) in the regulation of ZEB1 during EMT associated with prostate tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
303
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(322 citation statements)
references
References 52 publications
16
303
2
1
Order By: Relevance
“…showed that PI(3) kinase contributes to TrkB signaling as well (including anoikis resistance; Douma et al, 2004), in aggregate these data suggest a model in which TrkB activates multiple pathways, some of which critically depend on Zeb1 (Figure 7). Several reports have shown a correlation between Zeb1 expression and the aggressiveness of tumors, including those of endometrial (Spoelstra et al, 2006;Singh et al, 2008), colon (Pena et al, 2005;Aigner et al, 2007b), breast (Aigner et al, 2007a), lung (Dohadwala et al, 2006), gallbladder (Adachi et al, 2009), ovarian (Bendoraite et al, 2010) and prostate origin (Graham et al, 2008). In colon cancer, Zeb1 expression is linked to loss of the basement membrane, which correlates with increased metastasis (Spaderna et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…showed that PI(3) kinase contributes to TrkB signaling as well (including anoikis resistance; Douma et al, 2004), in aggregate these data suggest a model in which TrkB activates multiple pathways, some of which critically depend on Zeb1 (Figure 7). Several reports have shown a correlation between Zeb1 expression and the aggressiveness of tumors, including those of endometrial (Spoelstra et al, 2006;Singh et al, 2008), colon (Pena et al, 2005;Aigner et al, 2007b), breast (Aigner et al, 2007a), lung (Dohadwala et al, 2006), gallbladder (Adachi et al, 2009), ovarian (Bendoraite et al, 2010) and prostate origin (Graham et al, 2008). In colon cancer, Zeb1 expression is linked to loss of the basement membrane, which correlates with increased metastasis (Spaderna et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…ZEB1 and ZEB2 are able to initiate EMT by binding to E-boxes within the E-cadherin promoter and repressing its transcription, and silencing of ZEB1 was shown to increase the expression of E-cadherin (69,70). Downregulation of ZEB2 mRNA via ZEB2 siRNA in 4TO7 cells increased E-cadherin mRNA, and the cells that had stably silenced ZEB2 expression also adopted an epithelial-like morphology (25).…”
Section: Transcriptional Factorsmentioning
confidence: 98%
“…Actually, ZEB factors and miR200 reciprocally control their expression in a strict feedback loop [133]. Of note, ZEB1 is a key EMT regulator in many human cancers including prostate, colon, breast and pancreatic [132,[134][135][136], while miR200 family members are often down-regulated in cancer cells [131]. Actually, the regulation of EMT by miRNAs is a very general phenomenon not limited to TrkB signalling [137].…”
Section: Taddei Et Almentioning
confidence: 99%